Climate Change and Adaptation: Evidence from a Forest-dependent Community in Bangladesh (Journal of Forest and Livelihood, 2013)
DOI: http://dx.doi.org/10.3126/jfl.v11i1.8615 Journal of Forestry and Livelihood Vol.11(1) 2013 94-108